Teaching macroeconomics to the visually impaired: New tactile methods, verbal precision, and small groups. Issue 3 (3rd July 2017) - Naples, Michele I.
ABSTRACT: Visually-impaired students require tailored pedagogies to ensure their instruction is as high quality as for sighted students. They follow board work during class by referring to typed class notes provided ahead of time via a Braille reader, and in-class small groups solving problems create an inclusive esprit de corps and promote classmates' participation in clarifying board work. Small colleges with limited means can adopt Wikki Stix for tactile graphs that both artistically challenged faculty pressed for time and students can use successfully. Verbal description and "naming" (i.e., using analytical categories to identify sections of graphs) benefit visually-impaired and sighted students alike.